Netralitas Pegawai ASN dalam Pemilihan Umum (Catatan Kritis Pemilu Presiden 2024) - Bibianus Hengky Widhi Antoro (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
The General Election Commission (KPU) has inaugurated the elected Presidential and Vice Presidential Candidates in the 2024 General Election. All stages of the Presidential and Vice Presidential Elections have been passed, and we are just waiting to take the oath. Even though all stages have been carried out, various problems still need to be solved, one of which is related to the neutrality of civil servants. Data from the Commissioner of the Indonesian Civil Servant Commission and the Constitutional Court's decision shows that violations of Civil Servant neutrality are very high and massive, especially after enacting the latest Civil Servants Law. This article uses normative legal method with the statute, case, and conceptual approaches related to the issue of the Civil Servants neutrality in the 2024 presidential election is reviewed from of. The conclusion shows that many civil servants still violated neutrality, follow-up on recommendations still needed to be implemented, and future efforts were made to form an independent commission that was a single organ that was multi-tasked with dual functions, namely supervisory and quasi-judicial functions.